Impractical Python projects : playful programming activities to make you smarter - Vaughan, Lee (No Starch Press, Inc., 2019)
"A book of fun coding projects for readers who know a little Python already and want to expand their skills. Simulate volcanoes, map Mars, and more, while gaining experience using free modules like Tkinter, matplotlib, Cprofile, Pylint, Pygame, Pillow, and Python-Docx"--